THE CORNEA AND METHODS FOR MEASURING INTRAOCULAR PRESSURE - Jordanova, Elena Angel; Hentova-Sencanic, Paraskeva; Marjanovic, Ivan; Sencanin, Ivan; Stefanovic, Ivana; Baralic, Marko (Sanamed, 2022)
Introduction:The study aimed to assert the relationship between central corneal thickness (CCT) and intraocular pressure (IOP) measured by: Goldmann applanation tonometry (GAT) and Dynamic contour tonometry (DCT). Materials and Methods:The study included 150 patients with a mean age of 59.39± 13.12 years. Patients were divided into three groups: 50 primary open-angle glaucoma (POAG) patients, 50 ocular hypertension (OHT) patients, and 50 normal tension glaucoma (NTG) patients. IOP was determined using GAT and DCT. CCT was measured by ultrasound pachymetry. Results: IOP measured with DCT was higher than IOP measured with GAT (19.80± 3.67 mmHg vs 17.71±3.35 mmHg). A significant positive association between IOP measured with GAT and IOP measured with DCT was found in all patients (r= 0.867, p< 0.01). A significantly positive association between IOP measured with GAT and IOP measured with DCT in POAG (r=0.855,p 0.05). Conclusion: CCT-influenced IOP was measured by both methods, GAT and DCT. DCT can not replace GAT, but it is very useful, especially in cases where errors are in the IOP GAT measurement.
Keywords: Cornea; Intraocular pressure; Pachymetry